Assessing Working Capital Management and Performance of Listed Manufacturing Firms: Nigeria Evidence - G. T., Akinleye; Roseline , ADEBOBOYE (Information Management and Business Review, 2019)
This study assessed working capital management and performance of listed manufacturing firms in Nigeria 20 firms were sampled, over 10 years. The study employed static data analyses and panel Granger causality test. Result showed that average collection period exerts insignificant negative effect on return on capital employed of the sampled firms, while average collection period also exerts insignificant negative effect on earnings per share of the sampled firms. The result further showed that, average payment period exerts insignificant positive effect on return on capital employed of the sampled firms, but average payment period exerts insignificant negative effect on earnings per share of the sampled firms. The study concluded that, average collection period and average payment exert insignificant effect on return on capital employed of listed manufacturing firms in Nigeria, also; average collection period and average payment period exert insignificant effect on earnings per share of listed manufacturing firms in Nigeria. Hence manufacturing firms in Nigeria should objectively manage average collection period and also maintain a consistent improvement in return on capital employed and earnings per share of listed manufacturing firms in Nigeria.